2018
DOI: 10.7759/cureus.3129
|View full text |Cite|
|
Sign up to set email alerts
|

Neurogenic Stunned Myocardium: A Literature Review

Abstract: Neurogenic stunned myocardium (NSM) is defined as the occurrence of cardiac abnormalities due to neurological events such as stroke, seizures, etc. These events lead to dysfunction of the autonomic nervous system (ANS) and ultimately cause injury to the myocardium. The clinical features seen in NSM include elevated troponin level, left ventricular dysfunction, and changes on the electrocardiogram (ECG). However, these features are also seen in Takotsubo cardiomyopathy as well as in an acute coronary syndrome (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Pathological responses in the CNS can elicit, mainly through these mechanisms, abnormal effects in heart function, such as alteration of blood pressure and cardiac rhythm, alteration in the conduction of the electric impulses and (mainly transient) cardiomyopathies. Although a univocal classification of these cardiomyopathies is still not available, two main entities have been described: the neurologic stunned myocardium (NSM) [ 13 ] and the TTC [ 4 , 14 ]. In both, the pathophysiological mechanism resides probably in a catecholamine storm, triggered by an acute neurological injury in NSM (mainly in the caudal ventrolateral medulla, the tractus solitarius, the dorsal motor vagal nucleus and the posterior hypothalamus), by emotional or physical stress with consequent activation of hypotalamo-pituitary-adrenal and sympatho-adrenomedullary axis in TTC.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological responses in the CNS can elicit, mainly through these mechanisms, abnormal effects in heart function, such as alteration of blood pressure and cardiac rhythm, alteration in the conduction of the electric impulses and (mainly transient) cardiomyopathies. Although a univocal classification of these cardiomyopathies is still not available, two main entities have been described: the neurologic stunned myocardium (NSM) [ 13 ] and the TTC [ 4 , 14 ]. In both, the pathophysiological mechanism resides probably in a catecholamine storm, triggered by an acute neurological injury in NSM (mainly in the caudal ventrolateral medulla, the tractus solitarius, the dorsal motor vagal nucleus and the posterior hypothalamus), by emotional or physical stress with consequent activation of hypotalamo-pituitary-adrenal and sympatho-adrenomedullary axis in TTC.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 67,000 patients demonstrated that the annual risk for developing myocardial infarction after stroke is about 2%, followed by a 20% 10-year risk of myocardial ischaemia [60,62]. A common myocardial infarction-like manifestation is neurogenic stunned myocardium, which differs from traditional myocardial damage because of the absence of coronary artery occlusion [63].…”
Section: Acute Cardiac Dysfunctionmentioning
confidence: 99%
“…A stunned myocardium is defined as a state in which a given section of the myocardium manifests with a certain form of contractile abnormality. Similarly, a neurogenic stunned myocardium refers to cardiac abnormalities that occur as a result of neurological disorders, such as seizures, stroke, etc [11]. A neurogenic stunned myocardium occurs secondary to reversible posterior leukoencephalopathy, seizures, subarachnoid bleed, Guillain-Barre syndrome, stroke, and/or brain tumor [12].…”
Section: Table 2: the Fisher Scalementioning
confidence: 99%
“…These events result in autonomic nervous system dysfunction and cause myocardial injury. Clinical features associated with neurogenic stunned myocardium include left ventricular dysfunction, elevated troponin level, and changes on the electrocardiogram [11]. Stunned myocardium is characterized by reversible left ventricular dysfunction and may be caused by a subarachnoid hemorrhage.…”
Section: Table 2: the Fisher Scalementioning
confidence: 99%